2022
DOI: 10.4069/kjwhn.2022.12.23
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, infant, and perinatal mortality statistics and trends in Korea between 2018 and 2020

Abstract: Purpose: This study aimed to identify maternal, infant, and perinatal mortality using the national population data of South Korea between 2018 and 2020, and to analyze mortality rates according to characteristics such as age, date of death, and cause of death in each group. This study updates the most recent study using 2009 to 2017 data.Methods: Analyses of maternal, infant, and perinatal mortality were done with data identified through the supplementary investigation system for cases of death from the Census… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Notably, as reported in previous studies, Korea’s IMR has been declining; the relative and absolute disparities have tended to increase in recent years. 11 12 13 14 This is because the decline in IMR in other regions has slowed compared to that in Seoul, and various causes, including the distribution of medical resources, social determinants of health, and the physical environment, need to be considered to determine the cause. 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, as reported in previous studies, Korea’s IMR has been declining; the relative and absolute disparities have tended to increase in recent years. 11 12 13 14 This is because the decline in IMR in other regions has slowed compared to that in Seoul, and various causes, including the distribution of medical resources, social determinants of health, and the physical environment, need to be considered to determine the cause. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the IMR in Korea has been continuously declining, and we analyzed the IMR trend in 16 provinces and metropolitan cities using the Joinpoint regression method to confirm whether the IMR trends in each region are similar. 11 12 13 14 The annual percent change (APC) in the IMR by region was calculated. More specifically, a maximum of two join points was set for each model, and the average APCs (AAPCs) were calculated for each segment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This embolism is a rare puerperium complication, from which the number of deaths in Korea was 6, 9, and 10 in 2018, 2019, and 2020, respectively. The number of deaths per 100,0000 population was 1.8, 3.0, and 3.7 in 2018, 2019, and 2020 [ 12 ].…”
Section: Obituarymentioning
confidence: 99%
“…High-quality studies that fit our aims and scope will be welcomed from authors over the world.We have continued to publish English manuscripts at a steady rate, which will be meaningful for international readers to access our published content. Our collaborative work with Statistics Korea also continued in 2022, resulting in a statistics paper [3].…”
mentioning
confidence: 99%